2014
DOI: 10.1158/1078-0432.ccr-13-2429
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Classification of Malignant Pleural Mesothelioma: Identification of a Poor Prognosis Subgroup Linked to the Epithelial-to-Mesenchymal Transition

Abstract: Purpose: Despite research efforts to develop more effective diagnostic and therapeutic approaches, malignant pleural mesothelioma (MPM) prognosis remains poor. The assessment of tumor response to therapy can be improved by a deeper phenotypical classification of the tumor, with emphasis on its clinicobiological heterogeneity. The identification of molecular profiles is a powerful approach to better define MPM subclasses and targeted therapies.Experimental Design: Molecular subclasses were defined by transcript… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
170
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(188 citation statements)
references
References 56 publications
12
170
0
6
Order By: Relevance
“…Interestingly, in this study mutation analysis of BAP1, CDKN2A, CDKN2B, NF2, and TP53 was also performed and showed that the subgroup with better prognosis exhibited more frequent BAP1 genetic variants. 74 This observation is in keeping with the data obtained by Arzt et al 57 who found that lack of BAP1 protein expression in mesothelioma is associated with better survival.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, in this study mutation analysis of BAP1, CDKN2A, CDKN2B, NF2, and TP53 was also performed and showed that the subgroup with better prognosis exhibited more frequent BAP1 genetic variants. 74 This observation is in keeping with the data obtained by Arzt et al 57 who found that lack of BAP1 protein expression in mesothelioma is associated with better survival.…”
Section: Discussionsupporting
confidence: 89%
“…In our report of human BAP1 families (11), all of the available malignant mesothelioma specimens seen in BAP1 mutation carriers were of the epithelial type, although the significance of this finding could not be established because of the relatively small number of cases evaluated. In sporadic malignant mesothelioma, several groups have reported that somatic mutations of BAP1 occur primarily in epithelioid tumors (11,12,38), whereas…”
Section: Discussionmentioning
confidence: 99%
“…Also comparable, was the association of somatically inactivated BAP1 with the epithelioid MM subtype (36). Since BAP1 can influence the regulation of gene expression epigenetically or through deubiquitination of transcription factors (see below), it is plausible that these different patterns of gene expression can lead to variations in MM tumor subtypes (35,40,41).…”
Section: Unique MM Clinical Characteristics Associated With Bap1 Mutamentioning
confidence: 97%